RANCANG BANGUN ARTIFICIAL INTELLIGENCE SISTEM INFORMASI ADMINISTRASI PELAYANAN PELANGGAN TRAVEL BINA SARANA SHUTTLE - Bambang Nurcahya, Said; Santoso, Octaviani Ratna Sari; Wuri, Fransisca (LPPM Politeknik Pajajaran ICB Bandung, 2025)
Technology is changing very quickly and affecting the business world. This technological change cannot be separated from business in the field of travel from Jakarta to Bandung. Even though Travel Jakarta Bandung has a new competitor to the Jakarta Bandung fast train, woosh, certain classes of people still use the car travel mode of transportation. . Artificial Intelligence helps companies in cost efficiency, one of which is costs for reservations, payments and 24-hour automated customer service. The application of Artificial Intelligence in Bina Sarana travel customer offices for roundtrip Jakarta, Bandung trips has become a trend for urban communities who have domiciles, businesses or clients in different cities, so that they need easy and closer travel from their city of origin to their destination city at affordable costs. be one option. This research uses qualitative methodology, by conducting observations, interviews, forum group discussions and analyzing service systems using the internet system. It is hoped that this journal can become a reference for travel entrepreneurs, media, campus researchers and policy makers in improving business efficiency in the travel sector in Indonesia. The implementation of a travel customer service information system using Artificial Intelligence still needs to be perfected so that it can connect not only 24-hour online reservations, payments and tickets, but can enable digital financial institutions, food and beverage suppliers, fashion and online motorcycle taxis to work together in one application to facilitate movement and other basic material needs, due to customer needs in the field sometimes requiring one stop shopping at travel locations.